Answer:
Step-by-step explanation:
23x + xy - y + 3y + 5 - 20x + 6xy = 23x - 20x + xy + 6xy -y + 3y + 5
= 3x + 7xy + 2y + 5
Errors:1) The combined coefficients of the x terms should be 3x, not 43x
2) The coefficients of the y terms have been multiplied.
3) The constant was left off.
<u>Answer:</u>
- The solution of the inequality is x < -2.
<u>Step-by-step explanation:</u>
<u>Let's simplify the inequality first.</u>
- => -4x < 8
- => -4x/4 < 8/4
- => -x < 2
- => x < -2
Hence, <u>the solution of the inequality is</u><u> x < -2.</u>
Hoped this helped.
![BrainiacUser1357](https://tex.z-dn.net/?f=BrainiacUser1357)
1. 5/6
2. 3/4
3. 2/3
4. 1/6
5. 1/4
6. 1/2